Are People Willing to Pay for Eco-Labeled Wild Seafood? An Overview - Boscaino G., Sprovieri M., Attanasio M., Vitale S., Giosuè C., Biondo F., Bono G (European Journal of Sustainable Development, 2017)
In the last two decades, eco-labeled seafood has been becoming an instrument of sustainability directed towards consumers, addressing a market-based incentive for better management of fisheries. In this context, several studies across the countries have been conducted about how much consumers are willing to pay for fish caught by certifiably sustainable fishing activities. In this direction, the aim of this study was to systematize the available information about the willingness-topay (WTP) more for eco-labeled wild seafood. Therefore, only papers published on ISI journals were searched on “Web of Knowledge” and “SciVerse Scopus” platforms, using the combinations of the following key words: seafood, ecolabel, willingness, WTP and premium. The results were organized considering the following variables: taxa, species’ family, English name of the species, survey’s country, data collection, brand and the WTP. A worldwide increasing interest on ecolabel seafood emerged clearly, empathizing the progressive affirmation of an eco-centrism vision, mainly in the developed countries. Keywords: Eco-label, Willingness to pay, Seafood